2004
DOI: 10.1021/bi0489457
|View full text |Cite
|
Sign up to set email alerts
|

SERCA Structural Dynamics Induced by ATP and Calcium

Abstract: We have used time-resolved phosphorescence anisotropy (TPA) to probe rotational dynamics of the rabbit skeletal sarcoplasmic reticulum Ca-ATPase (SERCA), to test the hypothesis, generated from X-ray crystallography, that large-scale structural changes are induced by Ca in this system. Previous TPA studies on SERCA used primarily erythrosin 5'-isothiocyanate (ErITC), which binds to the nucleotide-binding domain and inactivates the enzyme. To investigate rotational dynamics of the active enzyme, we labeled SERCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…Consider that stabilization by multiple weak interactions depends on anisotropy, and thermally induced motion reduces electrostatic forces because of averaging effects by dipole rotations. In fact, spectroscopic studies have shown conformational heterogeneity of the ATPase protein (37), as well as prominent effects of ligands on the internal dynamics of the enzyme protein (17). Strong restraint of fluctuations is then observed upon acquisition of intermediate catalytic states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider that stabilization by multiple weak interactions depends on anisotropy, and thermally induced motion reduces electrostatic forces because of averaging effects by dipole rotations. In fact, spectroscopic studies have shown conformational heterogeneity of the ATPase protein (37), as well as prominent effects of ligands on the internal dynamics of the enzyme protein (17). Strong restraint of fluctuations is then observed upon acquisition of intermediate catalytic states.…”
Section: Discussionmentioning
confidence: 99%
“…3) does not involve a primary effect on the digestion pattern but rather a delay of the time course of digestion occurring with the same pattern (E1 or E2, respectively). This suggests that protection may be due to constraint of conformational fluctuations related to internal protein dynamics (17) and required for suitable interaction of the ATPase with the proteolytic enzyme. This is best demonstrated by comparing the ATPase digestion with trypsin at various temperatures.…”
Section: Temperature Dependence Of Proteolytic Digestion and Effects mentioning
confidence: 99%
“…Rabbit light skeletal SR vesicles were prepared using a method previously reported. 13 Rabbit muscles were harvested from the hind leg of New Zealand White rabbits and purified using a sucrose gradient. The result light skeletal SR contains 80% SERCA.…”
Section: Methodsmentioning
confidence: 99%
“…2,[8][9][10][11][12][13] However, fluorescence resonance energy transfer (FRET) in functionally reconstituted membranes has shown that PLB binds tightly to SERCA in both the presence and absence of micromolar [Ca 2C ], so Ca-dependent relief of inhibition must be due to structural rearrangement 0022-2836/$ -see front matter q 2006 Elsevier Ltd. All rights reserved.…”
Section: Relief Of Inhibition Does Not Require Plb Dissociation From mentioning
confidence: 99%